Polisemi Kekkou Bahasa Jepang: Analisis Wacana dengan Teori Speaking Dell Hymes - Mashuri, Muhammad (IZUMI, 2026)
This study examines the polysemic meaning of the Japanese word 結構 (kekkou) and its use in everyday communication. Through pragmatic analysis using Dell Hymes' SPEAKING theory, this study identifies two main functions of 結構 (kekkou): as an expression of satisfaction or approval and as a subtle rejection. This word is often used in Japanese culture to show politeness in both formal and informal communication, which requires understanding the context to avoid misunderstanding. Within an utterance, the polysemy 結構 (kekkou) has different meanings and uses. The purpose of this study is to analyze the use of polysemy 結構 (kekkou) in Japanese speech.  This study adopts a qualitative approach through discourse analysis. The data were taken from a set of data corpus collected by the National Institute for Japanese Language and Linguistics. The data were collected by the documentation method, namely by searching and selecting sentences or phrases containing the word 結構 (kekkou) from various sources. In addition, the data were analyzed using 8 components of speech event formation (SPEAKING). From the analysis, it can be concluded that the polysemy of結構 (kekkou)  in Japanese shows the flexibility of this language in various communication contexts, both formal and informal, and reflects the subtlety and politeness in Japanese culture.  gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor